PENGARUH KOMPETENSI APARATUR DAN PENERAPAN PENGANGGARAN BERBASIS KINERJA TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (Survei Pada Dinas Kabupaten Bone Provinsi Sulawesi Selatan) - Muhammad Yamin (Institut Agama Islam Negeri Bone, 2020)
AbstractThe aim of this study is to know the influence of the officer competence and the implementation of performance budgeting, on performance accountability of governmental institution. Survey the sum of 76 responders covering all head on duty, secretary on duty, lead on the area at 19 on agency of Bone South Celebes Province. Data have been collected by questioner. The tool of statistic analysis using path analysis. The result of this study indicates that the officer competence and the implementation of performance budgeting, have been significant influence, on performance accountability of governmental institution. It means that properly of performance accountability of governmental institution on agency of Bone South Celebes Province influenced by equal to 67,3%, and by equal to 33,7% influenced by other factors are not included into this study model. Kata Kunci: Kompetensi; Penganggaran; Akuntabilitas